PENGENDALIAN KUALITAS TWISTED CABLE DENGAN METODE SEVEN TOOLS DAN QUALITY CONTROL CIRCLE (QCC) DI PT VOKSEL ELECTRIC Tbk - Subawa Prakoso; Yunus Amara Putra (Institut Bisnis Muhammadiyah Bekasi, 2020)
Production planning increases every month, with the increase in planning it isnecessary to improve quality. PT Voksel Electric Tbk is a manufacturing industryengaged in the production of power cables, telecommunications, and fiber optics. The company tries to control the quality of its products to maintain quality in accordance with the company's vision, which is to become a world-class cable solution provider in Indonesia. The purpose of this study was to determine how to control the quality of Twisted Cable at PT Voksel electric Tbk using the seven tools and QCC methods. The increased production planning does not match the actual production. This is due to the level of production failure. In this study, the method used in quality control is seven tools that are used to analyze the causes of product failure rates. By using the PDCA cycle (plan, do, check, action) and by using seven tools as a tool to determine the cause and effect of the failure of the production process. The causes obtained are from gram dust, from the crust on visual insulation, and from powder materials. By controlling the quality using the seven tools method, it can reduce production process time, production costs, and increase production capacity from 700 km to 800 km. an increase in production capacity of 100 km provides a benefit ofRp. 470,000,000,00,-